Faktor-faktor yang Mempengaruhi Pengambilan Keputusan Investasi pada Usaha Mikro Kecil Menengah (UMKM) - Ermawati, Nanik; Khotimah, Tutik; Nindyasari, Ratih (Jurnal Maksipreneur, 2023)
This study aims to test accounting knowledge, knowledge of financial feasibility analysis, and financial feasibility support systems for making investment decisions in Micro, Small, and Medium Enterprises (MSMEs). The population of this research is the Lasem Batik SMEs. The sampling technique used in this study was purposive sampling. The samples obtained were 44 UMKM. The data analysis technique used in this research was multiple linear regression analysis. The results of this study indicate that accounting knowledge has an effect on the investment decision-making process, but knowledge of financial feasibility analysis and the financial feasibility support system have no effect on the investment decision-making process. The findings of this study can be used to support MSMEs in making investment decisions.